Research on the Comprehensive Evaluation Method of Tight Reservoir Effectiveness Based on Multiparameter Fusion - ZHANG Huafeng; QIU Longwei; WANG Jun; CHEN Ganghua; YANG Yongqiang; GUO Chunqing; HE Yulong (Cejing jishu)
Accurate determination of effective lower limit and establishment of effective standard of tight reservoirs are of great significance for effective reserves estimation and production increase in tight oil. Based on convolution neural network and multivariate statistical analysis, establishes a model for lithology identification and petrophysical facies interpretation of tight reservoirs, and establishes a multi-parameter fusion method for evaluating the effectiveness of tight reservoirs by combining petrophysical facies classification modeling and pore structure evaluation on the basis of reservoir characteristics description. The actual data processing results show that the prediction accuracy of the established lithology identification method is high, and the comprehensive evaluation results are in agreement with the data of oil test and production test. This paper comprehensively considers the main factors that affect the effectiveness of tight reservoirs, and combines the lithology, physical properties and pore structure types of tight reservoirs to establish a comprehensive effectiveness evaluation method, which can be effectively applied to the comprehensive evaluation of tight reservoirs effectiveness.